Faktor-Faktor Tingkat Kecemasan Perawat di Unit Stroke dalam Menghadapi Kegawatdaruratan dalam Masa Pasca Pandemi Covid-19 - Tri Wahyuni Ismoyowati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The emergence of Covid-19 at the end of 2019 caused anxiety in various circles. Nurses are at the forefront in handling and caring for patients 24 hours a day who are at high risk of exposure, which can cause anxiety. So research was needed with the aim of finding out the factors related to the level of anxiety of nurses in the stroke unit when facing emergencies during the Covid-19 pandemic. The design of this research was cross-sectional. This research involved all nurses in hospital stroke units in Yogyakarta in 2022, a total of 37 respondents. The data collection tool used was an anxiety level questionnaire which was a modification of HARS. Data were analyzed using the Spearman correlation test. The results of the analysis showed that the respondents were aged 46-55 years, had a D3 education, and had worked >10 years. The prevalence level of nurse anxiety was 21.62%. Furthermore, the p value for each factor was age = 0.271, education = 0.854, and length of service = 0.609. It was concluded that there was no relationship between age, education and length of service and the level of anxiety among nurses in the stroke unit when dealing with emergencies during the Covid-19 pandemic in hospitals in Yogyakarta.Keywords: Covid-19; Emergency; stroke unit; nurse anxiety ABSTRAK Munculnya Covid-19 di akhir tahun 2019 menimbulkan kecemasan di berbagai kalangan. Perawat merupakan garda terdepan dalam penanganan dan perawatan pasien selama 24 jam beresiko tinggi untuk terpapar, yang bisa menimbulkan kecemasan. Maka diperlukan penelitian dengan tujuan untuk mengetahui faktor-faktor yang berhubungan dengan tingkat kecemasan perawat di unit stroke dalam menghadapi kegawatdaruratan dalam masa pandemi Covid-19. Desain penelitian ini adalah cross-sectional. Penelitian ini melibatkan seluruh perawat di unit stroke rumah sakit di Yogyakarta pada tahun 2022, sejumlah 37 responden. Alat pengumpul data yang digunakan adalah kuesioner tingkat kecemasan yang merupakan modifikasi dari HARS. Data dianalisis menggunakan uji korelasi Spearman. Hasil analisis menunjukkan bahwa responden berusia 46-55 tahun, berpendidikan D3, dan memiliki masa kerja >10 tahun. Prevalensi tingkat kecemasan perawat adalah 21,62%. Selanjutnya nilai p untuk masing-masing faktor adalah usia = 0,271, pendidikan = 0,854, dan masa kerja = 0,609. Disimpulkan bahwa tidak ada hubungan antara usia, pendidikan dan masa kerja dengan tingkat kecemasan pada perawat di unit stroke dalam menghadapi kegawatdaruratan dalam masa pandemi Covid-19 rumah sakit di Yogyakarta.Kata kunci: Covid-19; kegawatdaruratan; unit stroke; kecemasan perawat